Efektivitas Pelatihan “Functional Marketing: Marketing Social Skills 101” Pada Karyawan Perusahaan Asuransi Umum PT. X - Rizqi Zulfa Qatrunnada; Tsalitsa Haura Syarifah; Ferdinan Leonardo Siahaan; Aisyah Aulia Putri (JIP (Jurnal Intervensi Psikologi), 2021)
This study aims to examine the effectiveness of “Functional Marketing: Marketing Social Skills 101” training in increasing marketing communication skills in General Insurance Company PT X. Research respondents were selected through purposive sampling technique aimed at 15 employees of the Marketing Department and the HR-Continuous Improvement Department of PT X. The quasi experimental used was the one-group pretest and posttest design. Analysis of the results used a non-parametric Wilcoxon Signed-Rank test with a significance value of .046 (p < 0.05). The result showed that there was a significant effect on increasing participants' understanding of marketing communication skills which included aspects of communication, active listening, and negotiation skills. In addition, participants also gave a positive evaluation about the entire implementation of the training program which includes aspects of training materials, training facilities, and training facilitators.